Effects of pelleting and diet type on growth performance, carcass yield, and iodine value of finishing pigs - Jeremiah E Nemechek; Michael D Tokach; Steven S Dritz; Robert D Goodband; Joel M DeRouchey; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2014)
A total of 288 pigs (PIC 327 × 1050, initially 107.0 lb BW) were used in an 87-d trial to determine the effects of diet form and corn oil on growth performance, carcass yield, and iodine value (IV) of growing-finishing pigs. Treatments were arranged in a 2 × 3 factorial with the main effects of diet form and oil source. The 2 diet forms were meal or pellet. The 3 dietary formulations were: (1) corn-soybean meal—based control, (2) control with 30% dried distillers grains with solubles (DDGS) and 19% wheat middlings, and (3) control with 3% corn oil. No diet form × diet formulation interactions were observed for growth performance, HCW, or carcass yield. Overall (d 0 to 87), pigs fed pelleted diets had increased (P<0.05) ADG, decreased (P<0.05) ADFI, and improved (P<0.05) F/G compared with pigs fed meal diets. Diet form did not influence HCW or carcass yield. Pigs fed diets containing DDGS and wheat middlings had decreased (P<0.05) ADG compared with pigs fed the control or corn oil diets. Feeding the corn oil diet resulted in decreased (P<0.05) ADFI compared with pigs fed the diet with DDGS and wheat middlings, with pigs fed the control diet intermediate. Feed efficiency followed dietary energy, with pigs fed the corn oil diet having the best (P<0.05) F/G, pigs fed DDGS and wheat middlings diet having the worst, and pigs fed the control intermediate. Pigs fed the diet with DDGS and wheat middlings had decreased (P<0.05) HCW and carcass yield compared with pigs fed the control or corn oil treatments. No interaction was detected between diet form and oil source for belly fat IV. Pigs fed pelleted diets had increased (P<0.05) belly fat IV compared with those fed meal diets, regardless of diet formulation. Belly fat IV was greatest (P<0.05) for pigs fed DDGS and wheat middlings, lowest for pigs fed the control, and intermediate for pigs fed the corn oil diets. An interactive effect between diet form and oil source was detected (P<0.05) for shoulder fat IV, caused by an increase in shoulder fat IV from feeding pelleted diets for the control or corn oil treatments. Thus, with the exception of the lack of increase in IV in pigs fed the pelleted DDGS and wheat middlings diet, feeding pelleted diets increased carcass fat IV. Furthermore, we found no evidence that the source of fat (endogenous vs. supplemental) in pelleted diets affected the IV response to pelleting.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Corn oil; DDGS; Diet form; Pelleting; Finishing pig